Pemanfaatan Drone Quadcopter Pengangkut Pelampung Pada Proses Penyelamatan Korban - Fahadzaki Hadar Prihantoro; Joko Subur; Suhirwan; Muhammad Taufiqurrohman; Sinung Widiyanto (FORTEI Regional VII Jawa Timur, 2025)
Abstract—This study aims to design and develop a quadcopter drone capable of carrying a rescue float, equipped with a GPS-based position monitoring system, to enhance the effectiveness of drowning victim rescue operations. The research background is based on the high number of drowning-related deaths—over 236,000 annually according to WHO—and the limitations of conventional rescue methods. The research methodology included a literature review, mechanical and electronic design of the drone, integration of components such as a Pixhawk flight controller, GPS, telemetry, and a float release mechanism using a servo, as well as the development of a position monitoring application. Testing phases covered manual flight trials, battery endurance, payload capacity, drop accuracy, and GPS system performance. The results showed that the drone could stably carry a swim board-type float weighing up to 400 grams and accurately release it on target. The average flight time was approximately 15 minutes without payload and around 10 minutes with the float attached. The GPS system and monitoring application successfully displayed the drone’s position in real-time with adequate accuracy. Overall, the system operated as intended, supporting Search and Rescue (SAR) operations in aquatic environments, and has the potential for further development to improve payload capacity, flight range, and navigation automation. Keywords—quadcopter drone, rescue float, GPS, water rescue, SAR. Abstrak—Penelitian ini bertujuan merancang dan membangun drone quadcopter pengangkut pelampung penyelamat dengan sistem monitoring posisi berbasis GPS untuk meningkatkan efektivitas operasi penyelamatan korban tenggelam. Latar belakang penelitian didasari tingginya angka kematian akibat tenggelam, yang menurut WHO melebihi 236.000 jiwa per tahun, serta keterbatasan metode penyelamatan konvensional. Metode penelitian meliputi studi literatur, perancangan mekanik dan elektronik drone, integrasi komponen seperti flight controller Pixhawk, GPS, telemetri, dan mekanisme pelepasan pelampung menggunakan servo, serta pembuatan aplikasi monitoring posisi. Tahap uji coba mencakup pengujian terbang manual, daya tahan baterai, kemampuan angkut pelampung, akurasi pelepasan, serta kinerja sistem GPS. Hasil pengujian menunjukkan drone mampu mengangkut pelampung tipe swim board berbobot hingga 400 gram dengan stabil, serta dapat melakukan pelepasan secara tepat sasaran. Waktu terbang rata-rata tanpa beban mencapai ±15 menit, sedangkan dengan beban pelampung ±10 menit. Sistem GPS dan aplikasi monitoring berhasil menampilkan posisi drone secara real-time dengan akurasi yang memadai. Keseluruhan sistem bekerja sesuai rancangan, mendukung operasi SAR (Search and Rescue) di perairan, dan berpotensi dikembangkan lebih lanjut untuk peningkatan kapasitas angkut, jangkauan terbang, dan otomatisasi navigasi. Kata Kunci—drone quadcopter, pelampung penyelamat, GPS, penyelamatan perairan, SAR.